1883 Wash. Sess. Laws 302, ch. 6, § 29, pt. 15 - (:unkn) unknown (General Publisher, 1883)
Authorized City of Snohomish to regulate and prohibit carrying concealed deadly weapons and to prohibit using guns, pistols, firearms, firecrackers, bombs, and explosives.
--
Keywords: CARRY - CONCEALED